Influence of processing conditions on the mechanical, tribological and fatigue performance of cold spray coating: a review. (3rd April 2022) - Kumar, Santosh
ABSTRACT: Cold spray is an emerging surface coating technology for rapidly developing thick coating, thin films and additive manufacturing of parts at relatively low temperatures. The low cost and scalability of a cold spray method make it promising for diverse industrial applications. Presently, the cold spray coating is widely used for the production of machine parts, materials and tools that requires the desired surface properties. However, the consideration of process parameters setting develops a reliable coating having high mechanical, tribological, fatigue and morphological properties for demanding coating applications. Hence, the aim of this paper is to study the effect of processing conditions (pressure and temperature of propellant gas, powder particle morphology and post-process treatments) on the tribological and mechanical properties of cold-sprayed coatings. Further, the effect of microstructure and processing conditions on the fatigue and static characteristics of cold spray material is also discussed.